Laminate, molded article, exterior member for vehicle, and method for manufacturing laminate
Patent Information
- Application Number
- CN202580024073.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-29
- Filing Date
- 2025-03-28
- Publication Date
- 2026-11-03
AI Technical Summary
When metal sheets with laminated coating replacement films are stamped, the coating replacement films are prone to deterioration in appearance due to heat and may peel off from the metal sheet.
A laminated structure containing a biaxially oriented polyester film is adopted, wherein the melting point of the first layer is higher than that of the second layer. By controlling the integral intensity ratio in the X-ray diffraction pattern, the crystallinity is ensured to be moderate, the hot pressing temperature is reduced, and the adhesion is improved through the adhesive layer.
It effectively prevents the appearance deterioration and peeling of the coating replacement film during stamping, and improves the heat resistance and bonding strength of the laminate.
Smart Images

Figure CN123036207A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to laminates, molded articles, vehicle exterior parts, and methods for manufacturing laminates. Background Technology
[0002] The exterior parts of a car, such as door panels, front fenders, roof, tailgate, and hood, are painted. Painting typically involves spraying paint onto metal sheets; this is known as spray painting.
[0003] However, spray painting has a high environmental impact because the paints used contain volatile organic compounds (VOCs). Furthermore, due to the repeated application of spray paint, a large space is required for its application.
[0004] Instead of coating the metal sheet, a method for laminating a coating alternative film onto the metal sheet has been proposed (see Patent Document 1). The coating alternative film of Patent Document 1 includes a coloring layer, thus enabling the metal sheet to be decorated or protected using the coating alternative film.
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: Japanese Patent Application Publication No. 2020-192787 Summary of the Invention
[0008] The problem the invention aims to solve
[0009] When manufacturing exterior automotive parts using metal sheets laminated with a coating substitute film, the metal sheets are sometimes stamped. The appearance of the coating substitute film can sometimes deteriorate due to the heat it receives during stamping. The coating substitute film can also sometimes peel off from the metal sheet after stamping.
[0010] The object of this invention is to provide a laminate that can reduce or prevent the peeling of the coating replacement film from the metal sheet, and can reduce or prevent the deterioration of the appearance of the coating replacement film that may occur due to heat applied to the coating replacement film during stamping of the laminate. A further object of this invention is to provide a molded article formed by stamping the laminate. A further object of this invention is to provide a vehicle exterior trim part formed by stamping the laminate.
[0011] Solution for solving the problem
[0012] In order to solve this problem, the present invention has the following [1] configuration. [1]
[0014] A stack comprising:
[0015] Metal plate; and
[0016] A coating alternative film laminated onto the metal plate.
[0017] The coating replacement film comprises a biaxially oriented polyester film, a coloring layer, and a surface protective layer.
[0018] The biaxially oriented polyester film comprises a first layer (hereinafter sometimes referred to as "layer B") and a second layer (hereinafter sometimes referred to as "layer A").
[0019] The first layer is located between the second layer and the coloring layer.
[0020] The first layer contains a first polyester comprising alkylene terephthalate units.
[0021] The second layer contains a second polyester comprising alkylene terephthalate units.
[0022] The melting point of the first layer is higher than that of the second layer.
[0023] In the X-ray diffraction pattern of the laminate, the integrated intensity of the diffraction peak representing at least the alkyl terephthalate units originating from the first polyester and the alkyl terephthalate units originating from the second polyester, relative to the integrated intensity of the diffraction peak representing at least the alkyl terephthalate units originating from the first polyester and the alkyl terephthalate units originating from the second polyester, is 0.2 or more and 1.0 or less, and the (1-10) plane is a crystal plane as follows:
[0024] .
[0025] It should be noted that the crystal plane cannot be entered as text in the online procedure for the Japan Patent Office. Therefore, in this specification, the crystal plane is referred to as the “(1-10) plane” which can be entered as text.
[0026] According to [1], coating replacement films contain a coloring layer, thus enabling the decoration or protection of metal sheets.
[0027] Furthermore, since the coating replacement film contains a surface protective layer, the coloring layer can be protected by the surface protective layer.
[0028] Furthermore, since the melting point of the first layer is higher than that of the second layer, i.e., the melting point of the second layer is lower than that of the first layer, the lamination temperature (specifically the hot-pressing temperature) can be reduced compared to the case where the biaxially oriented polyester film consists of only the first layer.
[0029] In the stack of [1], the ratio (hereinafter, sometimes referred to as the "first integral intensity") of the integrated intensity of the diffraction peak representing the (1-10) plane to the integrated intensity of the diffraction peak representing the (100) plane (hereinafter, sometimes referred to as the "second integral intensity") is determined, and the integral intensity ratio can be used as an indicator of crystallinity. This will be illustrated by taking a biaxially oriented polyethylene terephthalate (PET) film as an example. In a biaxially oriented PET film, the (100) plane of the PET crystal structure is a crystal plane containing benzene rings. The (100) plane is approximately parallel to the plane of the biaxially oriented PET film (which may also be called the "main plane"). On the other hand, the (1-10) plane of the PET crystal structure is a plane tilted relative to the (100) plane, and therefore oriented in multiple directions compared to the (100) plane. Therefore, in the X-ray diffraction pattern of a biaxially oriented PET film, the integral intensity of the diffraction peak representing the (1-10) plane is less affected by the crystallinity of PET than the integral intensity of the diffraction peak representing the (100) plane is affected by its crystallinity. Therefore, the smaller the ratio of the integral intensity of the diffraction peak representing the (1-10) plane to the integral intensity of the diffraction peak representing the (100) plane, the higher the crystallinity of PET. Therefore, this ratio can be used as an indicator of crystallinity. This principle also applies to biaxially oriented polyester films in the laminate [1]. Therefore, the integral intensity ratio (i.e., the ratio of the first integral intensity to the second integral intensity) can be used as an indicator of crystallinity.
[0030] According to the laminate [1], the integral strength ratio is less than 1.0, so the crystallinity will not become too low, thus improving the heat resistance of the biaxially oriented polyester film. Therefore, it is possible to reduce or prevent unevenness on the surface of the biaxially oriented polyester film that may occur due to the heat received by the coating substitute film during stamping of the laminate. As a result, it is possible to reduce or prevent the deterioration of the surface shape of the coating substitute film that may occur due to the heat. Therefore, it is possible to reduce or prevent the deterioration of the appearance (i.e., the appearance) of the coating substitute film that may occur due to the heat.
[0031] On the other hand, since the integral strength ratio is 0.2 or higher, the crystallinity will not be too high, thus avoiding the adhesion to the metal sheet becoming too low. Therefore, it is possible to reduce or prevent the occurrence of coating replacement film peeling off from the metal sheet, especially the occurrence of coating replacement film peeling off from the metal sheet after the laminate has been stamped.
[0032] The present invention preferably has the following configurations [2] to
[13] . [2]
[0034] According to the laminate described in [1], the coating replacement film further comprises an adhesive layer.
[0035] The adhesive layer is located between the biaxially oriented polyester film and the coloring layer. [3]
[0037] According to the laminate described in [2], the thickness of the adhesive layer is more than 10 nm and less than 200 nm. [4]
[0039] The laminate according to any one of [1] to [3], wherein the coloring layer contains a resin and a colorant. [5]
[0041] The laminate according to any one of [1] to [4], wherein the alkyl terephthalate unit of the first polyester comprises a polyethylene terephthalate unit.
[0042] The alkyl terephthalate unit of the second polyester comprises a polyethylene terephthalate unit.
[0043] The (1-10) facets are at least derived from the polyethylene terephthalate units of the first polyester and the polyethylene terephthalate units of the second polyester.
[0044] The (100) facet is at least derived from the polyethylene terephthalate unit of the first polyester and the polyethylene terephthalate unit of the second polyester. [6]
[0046] According to the laminate described in [5], when the repeating unit of the first polyester is set to 100 mol%, the polyethylene terephthalate unit is 85 mol% or more.
[0047] When the repeating unit of the second polyester is set to 100 mol%, the ethylene terephthalate unit is 60 mol% or more. [7]
[0049] The laminate according to any one of [1] to [6] further comprises a protective film.
[0050] The laminate consists of the metal plate, the coating replacement film, and the protective film stacked sequentially. [8]
[0052] The laminate according to any one of [1] to [7] is used to manufacture vehicle exterior parts. [9]
[0054] A molded article is formed by stamping any one of the laminates described in [1] to [8].
[10]
[0056] A vehicle exterior component is formed by stamping a laminated body as described in any one of [1] to [8].
[11]
[0058] A method for manufacturing a laminate, which is a method for manufacturing a laminate as described in any one of [1] to [8], comprising:
[0059] The process of heating the metal plate; and
[0060] The process of pressing the heated metal plate with the coating replacement film or composite film.
[0061] The composite film includes the coating replacement film and a protective film disposed on the surface protective layer of the coating replacement film.
[12]
[0063] The manufacturing method of the laminate according to
[11] further includes a step of starting cooling within 5 seconds after pressing the metal plate with the coating alternative film or the composite film.
[13]
[0065] According to the manufacturing method of the laminate described in
[11] or
[12] , the planar orientation coefficient of the first layer of the coating substitute film or the composite film pressed onto the metal plate is 0.165 or more and 0.180 or less.
[0066] The planar orientation coefficient of the second layer of the coating replacement film or the composite film pressed onto the metal plate is 0.100 or higher and 0.135 or lower.
[0067] The present invention also preferably has the following configuration.
[14]
[0069] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the metal sheet comprises an alloy sheet.
[15]
[0071] The laminate, molded article, vehicle exterior component, or method of manufacturing a laminate according to any one of the above-described components, wherein the metal plate comprises a steel plate, an aluminum alloy plate, or a magnesium alloy plate.
[16]
[0073] The laminate, molded article, vehicle exterior component, or method of manufacturing a laminate according to any one of the above-described components, wherein the metal sheet comprises a steel sheet coated with a zinc alloy.
[17]
[0075] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the thickness of the biaxially oriented polyester film is 10 μm or more or 15 μm or more.
[18]
[0077] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the thickness of the biaxially oriented polyester film is 20 μm or more or 30 μm or more.
[19]
[0079] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the thickness of the biaxially oriented polyester film is less than 200 μm or less than 150 μm.
[20]
[0081] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the thickness of the biaxially oriented polyester film is 100 μm or less or 75 μm or less. [twenty one]
[0083] According to any one of the above-described components, the laminate, molded article, vehicle exterior part, or method of manufacturing the laminate, wherein the sum of the thermal shrinkage rate in the flow direction and the thermal shrinkage rate in the width direction of the biaxially oriented polyester film during heat treatment at 150°C for 15 minutes is 5.0% or less or 4.8% or less. [twenty two]
[0085] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the sum of the thermal shrinkage rate in the flow direction and the thermal shrinkage rate in the width direction is 4.5% or less or 4.0% or less. [twenty three]
[0087] According to any one of the above-described components, the laminate, molded article, vehicle exterior part, or method of manufacturing the laminate, wherein the sum of the thermal shrinkage rate in the flow direction and the thermal shrinkage rate in the width direction is 1.0% or more or 2.0% or more. [twenty four]
[0089] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the sum of the thermal shrinkage rate in the flow direction and the thermal shrinkage rate in the width direction is 3.0% or more.
[25]
[0091] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the difference between the melting point of the first layer and the melting point of the second layer is 20°C or more or 25°C or more.
[26]
[0093] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the difference between the melting point of the first layer and the melting point of the second layer is 28°C or more or 30°C or more.
[27]
[0095] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the difference between the melting point of the first layer and the melting point of the second layer is less than 70°C or less than 60°C.
[28]
[0097] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the difference between the melting point of the first layer and the melting point of the second layer is less than 50°C.
[29]
[0099] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the ratio of the thickness of the first layer to the thickness of the second layer (i.e., the thickness of the first layer / the thickness of the second layer) is 1.5 or more or 2.0 or more.
[30]
[0101] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the ratio (i.e., the thickness of the first layer / the thickness of the second layer) is 10 or less or 8 or less.
[31]
[0103] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the ratio (i.e., the thickness of the first layer / the thickness of the second layer) is 6 or less.
[32]
[0105] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the thickness of the first layer is 20 μm or more or 25 μm or more.
[33]
[0107] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the thickness of the first layer is 30 μm or more.
[34]
[0109] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the thickness of the first layer is 150 μm or less or 100 μm or less.
[35]
[0111] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the thickness of the first layer is 75 μm or less or 50 μm or less.
[36]
[0113] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the melting point of the first layer is 250°C or higher or 252°C or higher.
[37]
[0115] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the melting point of the first layer is 253°C or higher.
[38]
[0117] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the melting point of the first layer is below 260°C or below 258°C.
[39]
[0119] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the face orientation coefficient of the first layer is 0.165 or more or 0.168 or more.
[40]
[0121] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the face orientation coefficient of the first layer is 0.170 or higher.
[41]
[0123] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the face orientation coefficient of the first layer is 0.180 or less or 0.178 or less.
[42]
[0125] According to any one of the above-described components, the laminate, molded article, vehicle exterior part, or method of manufacturing the laminate, wherein when the repeating unit of the first polyester is set to 100 mol%, the polyethylene terephthalate unit is 85 mol% or more or 90 mol% or more.
[43]
[0127] According to any one of the above-described components, the laminate, molded article, vehicle exterior part, or method of manufacturing the laminate, wherein when the repeating unit of the first polyester is set to 100 mol%, the polyethylene terephthalate unit is 95 mol% or more or 97 mol% or more.
[44]
[0129] The laminate, molded article, vehicle exterior part, or method of manufacturing the laminate according to any one of the above-described components, wherein the first polyester is a crystalline polyester.
[45]
[0131] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the first polyester is polyethylene terephthalate.
[46]
[0133] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the polyethylene terephthalate is a homopolymer polyethylene terephthalate or a copolymer polyethylene terephthalate.
[47]
[0135] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the first layer comprises inactive particles.
[48]
[0137] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the first layer comprises silicon dioxide particles.
[49]
[0139] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the thickness of the second layer is 5 μm or more or 10 μm or more.
[50]
[0141] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the thickness of the second layer is 30 μm or less or 25 μm or less.
[51]
[0143] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the thickness of the second layer is 20 μm or less or 15 μm or less.
[52]
[0145] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the surface orientation coefficient of the second layer is 0.135 or less or 0.132 or less.
[53]
[0147] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the face orientation coefficient of the second layer is 0.130 or less.
[54]
[0149] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the surface orientation coefficient of the second layer is 0.100 or more or 0.110 or more.
[55]
[0151] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the face orientation coefficient of the second layer is 0.112 or higher.
[56]
[0153] According to any one of the above-described components, the laminate, molded article, vehicle exterior part, or method of manufacturing the laminate, wherein when the repeating unit of the second polyester is set to 100 mol%, the polyethylene terephthalate unit is 60 mol% or more or 70 mol% or more.
[57]
[0155] According to any one of the above-described components, the laminate, molded article, vehicle exterior part, or method of manufacturing the laminate, wherein when the repeating unit of the second polyester is set to 100 mol%, the polyethylene terephthalate unit is 80 mol% or more or 82 mol% or more.
[58]
[0157] According to any one of the above-described components, the laminate, molded article, vehicle exterior part, or method of manufacturing the laminate, wherein when the repeating unit of the second polyester is set to 100 mol%, the polyethylene terephthalate unit is 96 mol% or less or 94 mol% or less.
[59]
[0159] According to any one of the above-described components, the laminate, molded article, vehicle exterior part, or method of manufacturing the laminate, wherein when the repeating unit of the second polyester is set to 100 mol%, the polyethylene terephthalate unit is 92 mol% or less or 90 mol% or less.
[60]
[0161] The laminate, molded article, vehicle exterior part, or method of manufacturing the laminate according to any one of the above-described components, wherein the second polyester is a crystalline polyester.
[61]
[0163] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the second polyester is polyethylene terephthalate.
[62]
[0165] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the polyethylene terephthalate of the second polyester is a copolymer polyethylene terephthalate.
[63]
[0167] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the integral strength ratio is 0.9 or less or 0.8 or less.
[64]
[0169] The laminate, molded article, vehicle exterior part, or method of manufacturing a laminate according to any one of the above-described components, wherein the integral strength ratio is 0.3 or more or 0.4 or more.
[65]
[0171] The manufacturing method of the laminate according to
[11] further includes a step of starting cooling within 3 seconds or 2 seconds after pressing the metal plate with the coating alternative film or the composite film.
[66]
[0173] The method for manufacturing a laminate according to any one of the above-described compositions includes cooling the metal plate to which the coating alternative film or the composite film is pressed using water at a temperature of 60°C or below or 45°C.
[67]
[0175] In the method for manufacturing a laminate according to any one of the above-described compositions, the metal plate to which the coating alternative film or the composite film is pressed is cooled using water at a temperature of 35°C or below or 30°C.
[68]
[0177] In the method for manufacturing a laminate according to any one of the above-described components, the metal plate to which the coating alternative film or the composite film is pressed is immersed in a water tank to cool it.
[0178] The effects of the invention
[0179] According to the present invention, a laminate can be provided that reduces or prevents the peeling of the coating replacement film from the metal sheet, and can reduce or prevent the deterioration of the appearance (i.e., the look) of the coating replacement film that may occur due to heat applied to the coating replacement film during stamping of the laminate. According to the present invention, a molded article formed by stamping the laminate can also be provided. The present invention can also provide vehicle exterior parts formed by stamping the laminate. Attached Figure Description
[0180] Figure 1 This is a schematic cross-sectional view of the laminated body in this embodiment.
[0181] Figure 2 This is an example of the X-ray diffraction pattern of the laminate in this embodiment. Here, the horizontal axis represents the 2θ angle, and the vertical axis represents the intensity of the diffracted X-rays. In this example, the diffraction peaks near 2θ=23° represent the diffraction peaks of the (1-10) plane of polyethylene terephthalate, and the diffraction peaks near 2θ=26° represent the diffraction peaks of the (100) plane of polyethylene terephthalate. Detailed Implementation
[0182] Hereinafter, embodiments of the present invention will be described in detail.
[0183] <1. Layered Structures>
[0184] like Figure 1 As shown, the laminate 4 includes a metal plate 5 and a composite film 7 laminated on the metal plate 5.
[0185] That is, the laminate 4 includes a metal plate 5 and a coating replacement film 8 laminated on the metal plate 5, and also includes a protective film 9. In the laminate 4, the metal plate 5, the coating replacement film 8 and the protective film 9 are stacked sequentially.
[0186] <1.1. Metal Plate>
[0187] As the metal sheet 5, alloy sheets such as steel sheets, aluminum alloy sheets, and magnesium alloy sheets can be used. Among these, steel sheets are preferred. Stainless steel sheets can be used as examples of steel sheets. They can undergo pretreatment such as zinc alloy plating or chrome plating. That is, the steel sheet can also be a surface-treated steel sheet. As surface-treated steel sheets, tin-plated steel sheets and tin-coated steel sheets can be used as examples. In particular, when the laminate 4 is used to manufacture vehicle exterior parts, the metal sheet 5 is preferably a steel sheet that has undergone zinc alloy plating. Zinc alloy plating can improve rust resistance.
[0188] The thickness of the metal sheet 5 can be, for example, 0.2 mm or more, 0.3 mm or more, 0.4 mm or more, or 0.6 mm or more. On the other hand, the thickness of the metal sheet 5 can be, for example, 1.4 mm or less, 1.2 mm or less, 1.0 mm or less, or 0.8 mm or less. For the sake of good formability, the thickness of the metal sheet 5 is preferably 0.2 mm or more and 1.4 mm or less, more preferably 0.3 mm or more and 1.2 mm or less, and even more preferably 0.3 mm or more and 1.0 mm or less. When the metal sheet 5 is a steel sheet coated with zinc alloy, the thickness of the metal sheet 5 is preferably 0.4 mm or more and 0.8 mm or less. When the metal sheet 5 is an aluminum alloy sheet, the thickness of the metal sheet 5 is preferably 0.6 mm or more and 1.2 mm or less.
[0189] <1.2. Composite Thin Films>
[0190] The composite film 7 includes a coating replacement film 8 and a protective film 9. In the composite film 7, the protective film 9 is disposed on the coating replacement film 8.
[0191] <1.2.1. Coating as an Alternative to Thin Films>
[0192] The coating alternative film 8 comprises a biaxially oriented polyester film 81, an adhesive layer 82, a coloring layer 83, and a surface protective layer (hereinafter sometimes referred to as a "hard coating") 84. In the coating alternative film 8, the biaxially oriented polyester film 81, the adhesive layer 82, the coloring layer 83, and the surface protective layer 84 are overlapped in sequence.
[0193] <1.2.1.1. Biaxially Oriented Polyester Film>
[0194] A biaxially oriented polyester film 81 is disposed on the metal plate 5. Specifically, the A layer 812 of the biaxially oriented polyester film 81 is disposed on the metal plate 5.
[0195] The thickness of the biaxially oriented polyester film 81 is preferably 10 μm or more, more preferably 15 μm or more, even more preferably 20 μm or more, and even more preferably 30 μm or more. If it is 10 μm or more, film formation is easier, and functional layers such as the coloring layer 83 and the surface protective layer 84 are also easier to form. Furthermore, it provides good operability when the coating replacement film 8 or the composite film 7 is laminated onto the metal plate 5. On the other hand, the thickness of the biaxially oriented polyester film 81 is preferably 200 μm or less, more preferably 150 μm or less, even more preferably 125 μm or less, even more preferably 100 μm or less, and even more preferably 75 μm or less. If it is 200 μm or less, the load required for stamping the laminate 4 can be prevented from becoming excessive.
[0196] The sum of the thermal shrinkage rates in the flow direction and the width direction of the biaxially oriented polyester film 81 during heat treatment at 150°C for 15 minutes is preferably 5.0% or less, more preferably 4.8% or less. The smaller this sum, the less thermal shrinkage of the biaxially oriented polyester film 81 may occur during lamination (specifically, during heat pressing) due to the heat received by the coating substitute film 8. Therefore, it is possible to suppress the reduction in adhesion to the metal sheet that may be caused by this thermal shrinkage. The smaller this sum, the less dimensional change of the coating substitute film 8 caused by heat generated during shearing when stamping the laminate 4. That is, the dimensional stability of the coating substitute film 8 is excellent. This sum can be, for example, 4.5% or less, 4.2% or less, or 4.0% or less. On the other hand, this sum can be 1.0% or more, 2.0% or more, or 3.0% or more. This sum can be controlled by stretching conditions and heat setting treatment conditions.
[0197] It should be noted that the heat shrinkage rate of biaxially oriented polyester film 81 can be calculated using the following formula.
[0198] Heat shrinkage rate (%) = {(L0-L) / L0} × 100
[0199] Here, L is the spacing of the markings after heat treatment (specifically, heat treatment at 150°C for 15 minutes), and L0 is the spacing of the markings before heat treatment (specifically, heat treatment at 150°C for 15 minutes).
[0200] The biaxially oriented polyester film 81 comprises a B layer (i.e., the first layer) 811 and an A layer (i.e., the second layer) 812. The B layer 811 is located between the A layer 812 and the coloring layer 83.
[0201] The melting point of layer B 811 (hereinafter, sometimes referred to as "TmB") is higher than that of layer A 812 (hereinafter, sometimes referred to as "TmA"). That is, the melting point of layer A 812 is lower than that of layer B 811. As a result, compared with the case where the biaxially oriented polyester film 81 is composed of only layer B 811, the lamination temperature (specifically the hot-pressing temperature) can be reduced.
[0202] The difference between the melting point of layer B 811 and the melting point of layer A 812 is preferably 20°C or more, more preferably 25°C or more, even more preferably 28°C or more, and even more preferably 30°C or more. If the difference is 20°C or more, it can reduce the deterioration of the surface shape of the biaxially oriented polyester film 81 that may occur during lamination (specifically, during hot pressing) due to the heat received by the coating substitute film 8, and it can also reduce the viscosity of layer A 812 during lamination (specifically, during hot pressing). On the other hand, the difference between the melting point of layer B 811 and the melting point of layer A 812 is preferably 70°C or less, more preferably 60°C or less, and even more preferably 50°C or less. If the difference is 70°C or less, the operability during film formation is good.
[0203] The ratio of the thickness of layer B 811 to the thickness of layer A 812 (i.e., the thickness of layer B 811 / the thickness of layer A 812) is preferably 1.5 or more, more preferably 2.0 or more. If it is 1.5 or more, it can reduce the deterioration of the appearance of the coating substitute film 8 that may occur due to heat received by the coating substitute film 8 during lamination (specifically, during hot pressing). Furthermore, it can further reduce or prevent the deterioration of the appearance of the coating substitute film 8 that may occur due to heat received by the coating substitute film 8 during stamping of the laminate 4. On the other hand, the ratio of the thickness of layer B 811 to the thickness of layer A 812 (i.e., the thickness of layer B 811 / the thickness of layer A 812) is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less.
[0204] The thickness of layer B 811 is preferably 20 μm or more, more preferably 25 μm or more, and even more preferably 30 μm or more. If it is 20 μm or more, it can reduce the deterioration of the surface shape of the biaxially oriented polyester film 81 that may occur during lamination (specifically, during hot pressing) due to the heat received by the coating substitute film 8. Furthermore, it can further reduce or prevent the deterioration of the appearance of the coating substitute film 8 that may occur during the stamping of the laminate 4 due to the heat received by the coating substitute film 8. The thickness of layer B 811 is preferably 150 μm or less, more preferably 100 μm or less, even more preferably 75 μm or less, and even more preferably 50 μm or less.
[0205] The melting point of layer B 811 is preferably 250°C or higher, more preferably 252°C or higher, and even more preferably 253°C or higher. On the other hand, the melting point of layer B 811 may be 260°C or lower, or 258°C or lower.
[0206] The planar orientation coefficient of layer B 811 is preferably 0.165 or higher, more preferably 0.168 or higher, and even more preferably 0.170 or higher. This is because a larger planar orientation coefficient of layer B 811 reduces the generation of wrinkles and bubbles that may occur in the coating substitute film 8 due to heat during lamination (specifically, during hot pressing). Furthermore, a larger planar orientation coefficient of layer B 811 tends to increase the resilience of the biaxially oriented polyester film 81 during stamping of the laminate 4. On the other hand, the planar orientation coefficient of layer B 811 is preferably 0.180 or lower, more preferably 0.178 or lower.
[0207] Layer B 811 contains a first polyester, i.e., a first polyester resin. The intrinsic viscosity of the first polyester is preferably 0.60 or higher. If it is 0.60 or higher, the generation of heat-degrading substances originating from low molecular weight components can be reduced. On the other hand, the intrinsic viscosity of the first polyester is preferably less than 0.95.
[0208] The first polyester comprises repeating units containing alkylene terephthalate units. That is, the repeating units of the first polyester comprise alkylene terephthalate units.
[0209] Examples of alkylene terephthalate units include polyethylene terephthalate, propylene terephthalate, and polybutylene terephthalate. Among these, polyethylene terephthalate is preferred.
[0210] When the repeating unit of the first polyester is set to 100 mol%, the alkylene terephthalate unit is preferably 85 mol% or more, more preferably 90 mol% or more, even more preferably 95 mol% or more, and even more preferably 97 mol% or more.
[0211] When the repeating unit of the first polyester is set to 100 mol%, the ethylene terephthalate unit is preferably 85 mol% or more, more preferably 90 mol% or more, even more preferably 95 mol% or more, and even more preferably 97 mol% or more.
[0212] The repeating unit of the first polyester may include other units. Examples of other units include, for example, alkylene isophthalate units and alkylene naphthalate units. Examples of alkylene isophthalate units include, for example, polyethylene isophthalate units, propylene isophthalate units, and polybutylene isophthalate units. Examples of alkylene naphthalate units include, for example, polyethylene naphthalate units, propylene naphthalate units, and polybutylene naphthalate units. Preferably, the repeating unit of the first polyester does not include alkylene isophthalate units.
[0213] The first polyester is preferably a crystalline polyester. If the first polyester is a crystalline polyester, uneven elongation of the coating substitute film 8 that may occur during the stamping of the laminate 4 can be reduced. This will be explained below. During the stamping of the laminate 4, the coating substitute film 8 is partially stretched due to the stamping process. If the B layer 811 of the biaxially oriented polyester film 81 contains a crystalline polyester, the crystallization of the crystalline polyester in the maximally stretched portion (i.e., the maximum deformation portion) can proceed further than in its periphery (i.e., the periphery of the maximum deformation portion). Therefore, at the beginning of the stamping process, the coating substitute film 8 easily elongates in the maximum deformation portion, but as the stamping process continues, the maximum deformation portion itself becomes difficult to elongate. As a result, its periphery (i.e., the periphery of the maximum deformation portion) gradually elongates. Therefore, it is possible to prevent the thickness of the maximum deformation portion from becoming too thin. Therefore, uneven elongation of the coating substitute film 8 can be reduced. Crystalline polyesters are polyesters that, in differential scanning calorimetry (DSC) curves, exhibit an endothermic peak of 0.05 J / g or higher at temperatures higher than the temperature at which the baseline shift corresponding to the glass transition temperature occurs, associated with crystal melting. In the DSC procedure used to obtain the DSC curve, a sample is cut from layer B, 811. 10 mg of the sample is heated to 290 °C at a rate of 20 °C / min, held isothermally for 3 minutes, quenched at 200 °C / min, and then heated to 290 °C at a rate of 10 °C / min. A DSC-60 differential scanning calorimeter is used in the DSC procedure.
[0214] Polyethylene terephthalate (PET) is preferred as the first polyester. Examples of PET include homopolymer PET and copolymer PET. Homopolymer PET is preferred. Homopolymer PET may contain diethylene glycol, a byproduct of its manufacturing process. On the other hand, dicarboxylic acids, particularly isophthalic acid, are used as copolymer components, especially to obtain copolymer PET. Examples of aromatic carboxylic acids include isophthalic acid, 2,6-naphthalenedicarboxylic acid, and 2,7-naphthalenedicarboxylic acid; aliphatic dicarboxylic acids include adipic acid, azelaic acid, sebacic acid, and decanedicarboxylic acid; and alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid. One or more of these can be used. Examples of copolymer components, particularly glycols, used to obtain copolymerized polyethylene terephthalate include aliphatic glycols such as trimethylene glycol (propylene glycol), butanediol, and hexanediol; and alicyclic glycols such as cyclohexanediol. One or more of these can be used. Isophthalic acid and sebacic acid are preferred, and isophthalic acid is more preferred.
[0215] When layer B 811 is set to 100% by mass, the content of the first polyester is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 75% by mass or more. When layer B 811 is set to 100% by mass, the content of the first polyester can be, for example, 80% by mass or more, 90% by mass or more, or 95% by mass or more. On the other hand, when layer B 811 is set to 100% by mass, the content of the first polyester can be, for example, 100% by mass, 99% by mass or less, 98% by mass or less, 95% by mass or less, or 90% by mass or less.
[0216] Layer B 811 may also contain additives. Examples of additives include coloring pigments, optical brighteners, inactive particles, antioxidants, heat stabilizers, UV absorbers, and antistatic agents. Examples of coloring pigments include inorganic and organic pigments. Inorganic pigments are preferred. Examples of inorganic pigments include alumina, titanium dioxide, calcium carbonate, and barium sulfate. Titanium dioxide is preferred when imparting hiding power to layer B 811. When layer B 811 is 100% by mass, the content of coloring pigment can be 2% by mass or more, 4% by mass or more, or 10% by mass or more. On the other hand, when layer B 811 is 100% by mass, the content of coloring pigment can be 50% by mass or less, 40% by mass or less, or 35% by mass or less. Optical brighteners can improve whiteness.
[0217] Inactive particles improve the operability of the biaxially oriented polyester film 81, specifically by improving its slip properties. Examples of inactive particles include polymers or copolymers of monomers selected from polystyrene, polymethyl acrylate, polyethyl acrylate, polymethyl methacrylate, polyethyl methacrylate, and divinylbenzene, as well as organic materials such as polytetrafluoroethylene, polyacrylonitrile, benzoguanamine, and organosilicon. Inorganic materials such as silica, kaolin, talc, and graphite are also possible. Among these, inorganic materials are preferred, and silica particles are more preferred. The particle size of the inactive particles is preferably 0.1 μm to 10 μm. When layer B 811 is set to 100% by mass, the content of inactive particles is preferably 0.002% by mass to 0.5% by mass.
[0218] Layer A 812 bonds metal plate 5 to layer B 811. Layer A 812 is located between metal plate 5 and layer B 811.
[0219] The thickness of layer A 812 is preferably 5 μm or more, more preferably 8 μm or more, and even more preferably 10 μm or more. If it is 5 μm or more, it can fill any unevenness that may exist in the metal plate 5, thus improving the adhesion to the metal plate 5. The thickness of layer A 812 is preferably 30 μm or less, more preferably 25 μm or less, even more preferably 20 μm or less, and even more preferably 15 μm or less.
[0220] The melting point of layer A 812 is preferably 160°C or higher, more preferably 180°C or higher, and even more preferably 200°C or higher. On the other hand, the melting point of layer A 812 is preferably 250°C or lower, more preferably 240°C or lower, and even more preferably 230°C or lower.
[0221] The planar orientation coefficient of layer A 812 is preferably 0.135 or less, more preferably 0.132 or less, and even more preferably 0.130 or less. If it is 0.135 or less, the adhesion to the metal plate 5 can be improved. On the other hand, the planar orientation coefficient of layer A 812 is preferably 0.100 or more, more preferably 0.110 or more, and even more preferably 0.112 or more.
[0222] Layer A 812 contains a second polyester, i.e., a second polyester resin. The intrinsic viscosity of the second polyester is preferably 0.60 or higher. On the other hand, the intrinsic viscosity of the first polyester is preferably less than 0.95. If it is less than 0.95, the viscosity of layer A 812 during lamination (specifically, during hot pressing) can be reduced, thereby improving the adhesion to the metal plate 5.
[0223] The second polyester comprises repeating units containing alkylene terephthalate units. That is, the repeating units of the second polyester comprise alkylene terephthalate units.
[0224] Examples of alkylene terephthalate units include polyethylene terephthalate, propylene terephthalate, and polybutylene terephthalate. Among these, polyethylene terephthalate is preferred.
[0225] When the repeating unit of the second polyester is set to 100 mol%, the alkyl terephthalate unit is preferably 60 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, and even more preferably 82 mol% or more. When the repeating unit of the second polyester is set to 100 mol%, the alkyl terephthalate unit is preferably 96 mol% or less, more preferably 94 mol% or less, even more preferably 92 mol% or less, and even more preferably 90 mol% or less.
[0226] When the repeating unit of the second polyester is set to 100 mol%, the polyethylene terephthalate unit is preferably 60 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, and even more preferably 82 mol% or more. When the repeating unit of the second polyester is set to 100 mol%, the polyethylene terephthalate unit is preferably 96 mol% or less, more preferably 94 mol% or less, even more preferably 92 mol% or less, and even more preferably 90 mol% or less.
[0227] The repeating unit of the second polyester preferably includes other units. Examples of other units include, for example, alkylene isophthalate units and alkylene naphthalate units. Examples of alkylene isophthalate units include, for example, polyethylene isophthalate units, propylene isophthalate units, and polybutylene isophthalate units. Examples of alkylene naphthalate units include, for example, polyethylene naphthalate units, propylene naphthalate units, and polybutylene naphthalate units. The repeating unit of the second polyester preferably includes alkylene isophthalate units. When the repeating unit of the second polyester is set to 100 mol%, the alkylene isophthalate unit is preferably 4 mol% or more, more preferably 6 mol% or more, further preferably 8 mol% or more, and even more preferably 10 mol% or more. When the repeating unit of the second polyester is set to 100 mol%, the alkylene isophthalate unit is preferably 40 mol% or less, more preferably 30 mol% or less, even more preferably 20 mol% or less, and even more preferably 18 mol% or less. The repeating unit of the first polyester preferably does not contain alkylene naphthalate units.
[0228] The second polyester is preferably a crystalline polyester. A crystalline polyester is defined as a polyester that, in differential scanning calorimetry (DSC) curves, exhibits an endothermic peak of 0.05 J / g or higher at temperatures higher than the temperature at which the baseline shift corresponding to the glass transition temperature occurs, associated with crystal melting. In the DSC measurement used to obtain the DSC curve, a sample is cut from layer A 812, and 10 mg of the sample is heated to 290°C at 20°C / min, held isothermally for 3 minutes, quenched at 200°C / min, and then heated to 290°C at 10°C / min. A DSC-60 type differential scanning calorimeter is used in the DSC measurement.
[0229] As the second polyester, copolymerized polyethylene terephthalate is preferred. The description of the copolymerized polyethylene terephthalate in the second polyester is redundant with the description of the copolymerized polyethylene terephthalate in the first polyester, and therefore is omitted. Therefore, the description of the copolymerized polyethylene terephthalate in the first polyester can also be treated as a description of the copolymerized polyethylene terephthalate in the second polyester.
[0230] When layer A 812 is set to 100% by mass, the content of the second polyester is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more. On the other hand, when layer A 812 is set to 100% by mass, the content of the second polyester can be, for example, 100% by mass, 99% by mass or less, 98% by mass or less, or 95% by mass or less.
[0231] Layer A, 812, may also contain additives. Examples of additives include coloring pigments, fluorescent whitening agents, inactive particles, antioxidants, heat stabilizers, ultraviolet absorbers, and antistatic agents.
[0232] The biaxially oriented polyester film 81 can be manufactured by biaxially stretching the unstretched polyester film after its production. For example, the biaxially oriented polyester film 81 can be manufactured by the following steps: feeding molding material (i.e., a polyester composition containing a first polyester) for forming layer B 811 to a first extruder and feeding molding material (specifically, a polyester composition containing a second polyester) for forming layer A 812 to a second extruder; then feeding molding material from the first extruder into a feed block and from the second extruder into the feed block, stacking these molding materials in the feed block; then melt-extruding the unstretched polyester film (hereinafter sometimes referred to as a "sheet") from the die; then curing the unstretched polyester film with a cooling roller; and finally biaxially stretching and heat-setting the unstretched polyester film. Alternatively, the material can be produced through the following steps: raw materials for forming layer B 811 are supplied to a first extruder, and raw materials for forming layer A 812 are supplied to a second extruder. Then, molding materials are introduced from the first extruder into a manifold die, and molding materials are also introduced from the second extruder into the manifold die. These molding materials are then stacked in the manifold die. Next, an unstretched polyester film is melt-extruded from the manifold die. Then, the unstretched polyester film is cured using cooling rollers, and the unstretched polyester film is biaxially stretched and heat-set. Biaxial stretching can be simultaneous longitudinal and transverse biaxial stretching, or sequential biaxial stretching. Sequential biaxial stretching is preferred. In sequential biaxial stretching, for example, it is preferable to stretch the sheet that has passed through the cooling rollers along the flow direction, i.e., the longitudinal direction (Machine Direction) (hereinafter referred to as the "MD direction"), and then stretch the sheet after stretching in the MD direction along the width direction, i.e., the transverse direction (hereinafter referred to as the "TD direction"). It should be noted that surface treatment can be performed on the sheet between the first stretch (e.g., stretching in the flow direction) and the second stretch (e.g., stretching in the width direction). For example, an adhesive layer 82 can also be formed between the first stretch and the second stretch.
[0233] Regarding extrusion, in the first extruder, it is preferable to feed the molding material for forming layer B 811, i.e., the polyester composition containing the first polyester, after thorough drying, to the first extruder and melt it at a temperature of the melting point of the first polyester to (melting point + 50)°C. On the other hand, in the second extruder, it is preferable to feed the molding material for forming layer A 812, i.e., the polyester composition containing the second polyester, after thorough drying, to the second extruder and melt it at a temperature of the melting point of the second polyester to (melting point + 50)°C. It should be noted that at least one of the molding material for forming layer B 811 and the molding material for forming layer A 812 may contain inactive particles.
[0234] In the case of successive biaxial stretching, the unstretched polyester film can be heated and stretched along the flow direction. Examples of heating methods for the unstretched polyester film include roller heating and infrared heating. The stretching temperature in the flow direction is preferably 70°C or higher, more preferably 80°C or higher. A temperature of 70°C or higher reduces the occurrence of breakage. On the other hand, the stretching temperature in the flow direction is preferably 110°C or lower, more preferably 100°C or lower. A temperature of 110°C or lower prevents the orientation from becoming too low.
[0235] The stretch ratio in the flow direction is preferably 3.0 times or more, more preferably 3.5 times or more. A stretch ratio of 3.0 times or more helps prevent the orientation from becoming too low. Furthermore, it reduces or avoids excessive thickness unevenness, and reduces or avoids excessive slack that may occur when the biaxially oriented polyester film 81 is wound into a roll. On the other hand, the stretch ratio in the flow direction is preferably 5.0 times or less, more preferably 4.5 times or less, and even more preferably 4.0 times or less. A stretch ratio of 5.0 times or less effectively improves the thickness unevenness caused by stretching. An example of a stretching method in the flow direction is to stretch a heated, unstretched polyester film using a speed difference between rollers.
[0236] The polyester film, after being stretched in the flow direction, can be stretched along its width. The stretching temperature in the width direction is preferably 90°C or higher. A temperature of 90°C or higher reduces the occurrence of breakage. Conversely, the stretching temperature in the width direction is preferably 130°C or lower. A temperature of 130°C or lower prevents the orientation from becoming too low.
[0237] The stretch ratio in the width direction is preferably 3.0 times or more, more preferably 3.5 times or more. A stretch ratio of 3.0 times or more helps prevent the orientation from becoming too low. Furthermore, it reduces or avoids excessive thickness unevenness and reduces or avoids excessive slack that may occur when the biaxially oriented polyester film 81 is wound into a roll. On the other hand, the stretch ratio in the width direction is preferably 5.0 times or less, more preferably 4.5 times or less. A stretch ratio of 5.0 times or less effectively improves the thickness unevenness caused by stretching.
[0238] It is preferable to perform heat setting after biaxial stretching. Examples of heat setting temperatures include 150°C and above, but below 230°C. The heat setting temperature can be set according to the type of the first polyester and the type of the second polyester. When the first polyester is polyethylene terephthalate and the second polyester is a copolymer of polyethylene terephthalate, the heat setting temperature is preferably below 225°C, more preferably below 222°C, and even more preferably below 220°C. If the temperature is below 225°C, the crystallinity of the biaxially oriented polyester film 81 before lamination can be prevented from becoming too high, thus avoiding excessively mild face orientation. On the other hand, the heat setting temperature is preferably above 205°C, more preferably above 210°C, and even more preferably above 213°C. The heat setting temperature can be above 215°C. If the temperature is above 205°C, the crystallinity of the biaxially oriented polyester film 81 before lamination can be prevented from becoming too low.
[0239] The thermal relaxation process is preferably performed together with or separately from the heat setting process. In the thermal relaxation process, relaxation is preferably performed in at least one direction, either the flow direction (i.e., the MD direction) or the width direction (i.e., the TD direction). Of these, relaxation is preferably performed in the width direction. When relaxation is performed in the width direction, the relaxation rate in the width direction is preferably 3% or more, more preferably 4% or more. On the other hand, the relaxation rate in the width direction is preferably 8% or less, more preferably 7% or less.
[0240] <1.2.1.2. Adhesive Layer>
[0241] The adhesive layer 82 is located between the biaxially oriented polyester film 81 and the coloring layer 83. Specifically, the adhesive layer 82 is located between layer B 811 of the biaxially oriented polyester film 81 and the coloring layer 83. The adhesive layer 82 improves the adhesion between the biaxially oriented polyester film 81 and the coloring layer 83. Mechanisms for improving adhesion include, for example, the formation of bonds between functional groups, the reduction of interlayer interfacial energy, and interlayer interfacial mixing. It should be noted that the adhesive layer 82 can also be referred to as the easy-to-adhere layer 82.
[0242] From the viewpoint of adhesion, the thickness of the adhesive layer 82 is preferably 10 nm or more, more preferably 15 nm or more, even more preferably 20 nm, and even more preferably 40 nm or more. On the other hand, from the viewpoint of thickness uniformity and adhesion, the thickness of the adhesive layer 82 is preferably 200 nm or less, more preferably 180 nm, even more preferably 150 nm, and even more preferably 120 nm or less.
[0243] The adhesive layer 82 contains a resin. Examples of resins include polyurethane resins, vinyl chloride / vinyl acetate copolymer resins, vinyl chloride / vinyl acetate / acrylic copolymer resins, chlorinated polypropylene resins, acrylic resins, polyester resins, polyamide resins, butyraldehyde resins, polystyrene resins, nitrocellulose resins, and cellulose acetate resins. One or more of these can be used. Among these, acrylic resins and polyester resins are preferred. It should be noted that during the stamping of the laminate 4, heat is sometimes generated due to shearing, and the laminate 4 reaches approximately 150°C. Therefore, the glass transition temperature of the resin is preferably below 150°C. Furthermore, the adhesive layer 82 preferably does not contain polyesters comprising alkylene terephthalate units.
[0244] The resin preferably has at least one functional group selected from the group consisting of epoxy, oxazoline, silanol, and isocyanate groups. Among these, epoxy and oxazoline groups are preferred as functional groups from the viewpoint of further improving the adhesion to layer B 811.
[0245] The adhesive layer 82 can be formed on the biaxially oriented polyester film 81 by any method. For example, the adhesive layer 82 can be formed by online coating during the film-making process of the biaxially oriented polyester film 81. Alternatively, the adhesive layer 82 can be formed by offline coating after the biaxially oriented polyester film 81 is film-made, wound into a roll, and then pulled out for coating.
[0246] <1.2.1.3. Shading Layer>
[0247] A coloring layer 83 is located between the adhesive layer 82 and the surface protective layer 84. The coloring layer 83 is disposed on the adhesive layer 82. The coloring layer 83 can decorate or protect the metal plate 5.
[0248] The thickness of the coloring layer 83 is preferably 2 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more. On the other hand, the thickness of the coloring layer 83 is preferably 100 μm or less, more preferably 75 μm or less, even more preferably 50 μm or less, even more preferably 40 μm or less, and even more preferably 30 μm or less. It should be noted that the coloring layer 83 can be a single layer or multiple layers.
[0249] Coloring layer 83 contains a colorant. Examples of colorants include pigments and dyes. Examples of pigments and dyes include carbon black, iron black, titanium dioxide, antimony white, chrome yellow, titanium yellow, iron oxide red, cadmium red, ultramarine, cobalt blue, quinacridone red, isoindolinone yellow, phthalocyanine blue, aluminum, brass, titanium dioxide, and pearlescent pigments. As described above, coloring layer 83 can be a single layer or a multilayer structure. For example, when coloring layer 83 is a double layer, it is sometimes preferable that one of the layers contains a glossy pigment. For example, when coloring layer 83 is a double layer, it is sometimes preferable that the layer closest to the biaxially oriented polyester film 81 contains an aluminum pigment, and the layer closest to the surface protective layer 84 contains a pigment.
[0250] When the coloring layer 83 is set to 100% by mass, the content of the colorant is preferably 0.5% by mass or more, more preferably 2% by mass or more, and even more preferably 5% by mass or more. On the other hand, when the coloring layer 83 is set to 100% by mass, the content of the colorant is preferably 40% by mass or less, more preferably 30% by mass or less, and even more preferably 25% by mass or less.
[0251] The coloring layer 83 preferably contains a resin (hereinafter, sometimes referred to as "adhesive resin"). Because the coloring layer 83 contains an adhesive resin, the generation of cracks in the coloring layer 83 can be reduced during the stamping of the laminate 4. Examples of adhesive resins include acrylic resins, polyurethane resins, polyester resins, and PVDF (polyvinylidene fluoride). One or more of these can be used. Among them, acrylic resins are preferred. It should be noted that the coloring layer 83 preferably does not contain polyesters containing alkylene terephthalate units.
[0252] The coloring layer 83 can be formed on the adhesive layer 82 by any method. For the reason that the coloring layer 83 can be easily formed, coating is preferred.
[0253] <1.2.1.4. Surface Protective Layer>
[0254] A surface protective layer 84 is disposed on the coloring layer 83. The surface protective layer 84 reduces potential damage to the coloring layer 83 and the biaxially oriented polyester film 81 (i.e., improves damage resistance). Furthermore, the surface protective layer 84 can sometimes improve adhesion to the protective film 9. The surface protective layer 84 is preferably transparent. The surface protective layer 84 is preferably weather-resistant. The surface protective layer 84 may also be glossy.
[0255] The thickness of the surface protective layer 84 is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 15 μm or more. This is because a thicker surface protective layer 84 reduces potential damage to the coloring layer 83 and the biaxially oriented polyester film 81 (i.e., improves damage resistance) and also improves chemical resistance. On the other hand, the thickness of the surface protective layer 84 is preferably 80 μm or less, more preferably 60 μm or less, and even more preferably 50 μm or less. This is because a thinner surface protective layer 84 is more economical. It should be noted that the surface protective layer 84 can be a single layer or a multilayer structure.
[0256] The surface protective layer 84 preferably contains at least one of a thermosetting resin and a photocurable resin. That is, the surface protective layer 84 preferably has thermocurability or photocurability. Thermocurability is preferred. Specifically, the surface protective layer 84 preferably contains a thermosetting resin. This is because, during the stamping of the laminate 4, heat generated by shearing can be used for thermosetting. Examples of thermosetting resins include acrylic resins, melamine resins, and polyurethane resins. Acrylic resins are preferred. One or more of these resins can be used. It should be noted that the surface protective layer 84 preferably does not contain polyesters containing alkylene terephthalate units. The surface protective layer 84 preferably contains a crosslinking agent. The surface protective layer 84 may also contain other additives.
[0257] The curing degree of the surface protective layer 84 can be either fully cured or partially cured. Here, fully cured means the curing has reached its final state. On the other hand, partially cured means the curing has not reached its final state. Partially cured is preferred. This is because, during the stamping of the laminate 4, the surface protective layer 84 can effectively follow the deformation of the metal sheet 5. When the surface protective layer 84 contains a thermosetting resin, the curing degree of the surface protective layer 84 is preferably partially thermo-cured. The curing degree can be, for example, stage B.
[0258] The surface protective layer 84 can be formed on the coloring layer 83 by any method. For example, the surface protective layer 84 can be formed by coating, melt extrusion, lamination, etc. Among these, coating is preferred because it facilitates the formation of the surface protective layer 84. It should be noted that when a two-layer surface protective layer 84 is formed, that is, when the coating used to form the surface protective layer 84 is applied twice, the curing degree of each layer can be adjusted by changing the drying conditions in the first and second applications.
[0259] <1.2.2. Protective Film>
[0260] A protective film 9 is disposed on the surface protective layer 84 of the coating replacement film 8. The protective film 9 can prevent damage to the coating replacement film 8 and prevent contaminants from adhering to the coating replacement film 8.
[0261] The thickness of the protective film 9 is preferably 10 μm or more, more preferably 25 μm or more, and even more preferably 38 μm or more. A thickness of 10 μm or more results in excellent rigidity. The thickness of the protective film 9 is preferably 150 μm or less, more preferably 100 μm or less, even more preferably 75 μm or less, and even more preferably 50 μm or less. This is because a thinner protective film 9 is more economical. It should be noted that the protective film 9 can be a single layer or multiple layers.
[0262] The protective film 9 may contain a resin. Examples of resins include polyethylene resin, polyester resin, polypropylene resin, and polyvinyl chloride resin. Examples of polyester resins include homopolymer polyester resin and copolymer polyester resin. One or more of these can be used. Polyester resin is preferred from the perspective of excellent heat resistance and ability to reduce uneven elongation of the coating replacement film 8. Polyethylene resin is also preferred.
[0263] The surface roughness of at least one of the two sides of the protective film 9 that is in contact with the hard coating is preferably 1 nm or more, more preferably 3 nm or more, and even more preferably 10 nm or more. If it is 10 nm or more, the protective film 9 has good transportability and therefore good operability. The surface roughness is preferably 1000 nm or less, more preferably 800 nm or less, and even more preferably 500 nm or less. The surface shape of the protective film 9 can be transferred to the surface protective layer 84. If the surface roughness is 1000 nm or less, the appearance of the surface protective layer 84 can be prevented from deteriorating.
[0264] Preferably, at least one of the two sides of the protective film 9 that is in contact with the surface protective layer 84 is subjected to a peeling treatment. For example, a silicone-based peeling agent, a fluorinated peeling agent, or a long-chain aliphatic peeling agent can be used for the peeling treatment. Among these, a silicone-based peeling agent is preferred due to its lower cost.
[0265] The protective film 9 can be formed on the surface protective layer 84 of the coating substitute film 8 by any method. For example, the protective film 9 can be formed by coating, melt extrusion, lamination, etc. Among these, lamination, that is, laminating the protective film 9 onto the coating substitute film 8, is preferred.
[0266] <1.3. Integral Intensity Ratio>
[0267] In the laminate 4, the integral intensity ratio (i.e., the ratio of the first integral intensity to the second integral intensity) is 0.2 or more and 1.0 or less. The first integral intensity represents the integral intensity of the diffraction peaks on the (1-10) plane of at least the alkyl terephthalate units of the first polyester and the alkyl terephthalate units of the second polyester. The second integral intensity represents the integral intensity of the diffraction peaks on the (100) plane of at least the alkyl terephthalate units of the first polyester and the alkyl terephthalate units of the second polyester. Here, the (1-10) plane is preferably the (1-10) plane of the polyethylene terephthalate crystal. Therefore, the first integral intensity is preferably the integral intensity of the diffraction peaks on the (1-10) plane of at least the polyethylene terephthalate. On the other hand, the (100) plane is preferably the (100) plane of the polyethylene terephthalate crystal. Therefore, the second integral intensity is preferably the integral intensity representing the diffraction peak of at least the (100) plane of polyethylene terephthalate. An example of the X-ray diffraction pattern of the laminate 4 is shown below. Figure 2 .
[0268] The integral intensity ratio can be used as an indicator of crystallinity. This can be illustrated by taking a biaxially oriented polyethylene terephthalate (PET) film as an example. In a biaxially oriented PET film, the (100) plane of the PET crystal structure is a crystal plane containing benzene rings.
[0269] The (100) plane is approximately parallel to the plane of the biaxially oriented PET film (which can also be called the "master plane"). On the other hand, the (1-10) plane of the PET crystal structure is tilted relative to the (100) plane, and therefore faces in multiple directions compared to the (100) plane. Therefore, in the X-ray diffraction pattern of the biaxially oriented PET film, the integral intensity of the diffraction peak representing the (1-10) plane is less affected by the crystallinity of PET than the integral intensity of the diffraction peak representing the (100) plane is affected by it (i.e., the crystallinity of PET). Therefore, the smaller the ratio of the integral intensity of the diffraction peak representing the (1-10) plane to the integral intensity of the diffraction peak representing the (100) plane, the higher the crystallinity of PET. Therefore, this ratio can be positioned as an indicator of crystallinity. This principle also holds true in the biaxially oriented polyester film 81 of the laminate 4. Therefore, the integral intensity ratio (i.e., the ratio of the first integral intensity to the second integral intensity) can be positioned as an indicator of crystallinity.
[0270] With an integral intensity ratio of 1.0 or less, the crystallinity does not become excessively low, thus improving the heat resistance of the biaxially oriented polyester film 81. Therefore, it is possible to reduce or prevent unevenness on the surface of the biaxially oriented polyester film 81 that may occur due to heat received by the coating substitute film 8 during stamping of the laminate 4. Consequently, it is possible to reduce or prevent the deterioration of the surface shape of the coating substitute film 8 that may occur due to this heat. Therefore, it is possible to reduce or prevent the deterioration of the appearance (i.e., the physical appearance) of the coating substitute film 8 that may occur due to this heat.
[0271] The integral strength ratio is preferably below 0.9. The integral strength ratio can be below 0.8, below 0.7, below 0.6, or below 0.5.
[0272] On the other hand, since the integral strength ratio is 0.2 or higher, the crystallinity will not be too high, thus avoiding the adhesion to the metal plate 5 becoming too low. Therefore, it is possible to reduce or prevent the occurrence of coating replacement film 8 peeling off from the metal plate 5, especially the occurrence of coating replacement film 8 peeling off from the metal plate 5 after the laminate 4 is stamped.
[0273] The integral strength ratio is preferably 0.3 or higher. The integral strength ratio can be 0.4 or higher, 0.5 or higher, 0.6 or higher, or 0.7 or higher.
[0274] The integral intensity ratio can be controlled, for example, by the heat-setting temperature and the lamination temperature (specifically, the hot-pressing temperature). A higher heat-setting temperature results in increased crystallinity of the biaxially oriented polyester film 81 before lamination, thus decreasing the integral intensity ratio. A higher lamination temperature (specifically, the hot-pressing temperature) allows for greater crystal melting, thus increasing the integral intensity ratio. It should be noted that the integral intensity ratio is also affected by the type of the first polyester, the type of the second polyester, the stretching temperature, and the stretching ratio. It should also be noted that when the laminate 4 includes the protective film 9, X-ray diffraction (i.e., X-ray diffraction intensity measurement) is performed after the protective film 9 is peeled off.
[0275] <1.4. Manufacturing method of laminated body>
[0276] The manufacturing method of the laminate 4 includes a step of pressing a heated metal plate 5 with a coating substitute film 8 or a composite film 7 (hereinafter sometimes referred to as the "pressing step"). Preferably, the manufacturing method of the laminate 4 also includes a step of heating the metal plate 5 (hereinafter sometimes referred to as the "heating step") and a step of cooling the metal plate 5 with the coating substitute film 8 or composite film 7 pressed on it (hereinafter sometimes referred to as the "cooling step"). It should be noted that when the metal plate 5 is in a roll and the coating substitute film 8 or composite film 7 is also in a roll, the laminate 4 can be manufactured by roll-to-roll.
[0277] <1.4.1. Process of heating metal plate>
[0278] In this process, the metal plate 5 is heated. By heating the metal plate 5, it is possible to heat-press the metal plate 5 with the coating replacement film 8 or the composite film 7.
[0279] <1.4.2. Crimping Process>
[0280] In this process, a heated metal plate 5 is pressed together with a coating replacement film 8 or a composite film 7. Specifically, the two are pressed together with the A layer 812 of the coating replacement film 8 or the A layer 812 of the composite film 7 facing the heated metal plate 5.
[0281] In this process, the temperature of the heated metal plate 5 is preferably above the melting point of layer A 812. If it is above the melting point of layer A 812, layer A 812 can be melted, thus allowing the metal plate 5 to be heat-pressed onto the coating replacement film 8 or composite film 7. More preferably, the temperature of the heated metal plate 5 is above the combined temperature of the melting point of layer A 812 and 20°C, even more preferably above the combined temperature of the melting point of layer A 812 and 30°C, even more preferably above the combined temperature of the melting point of layer A 812 and 35°C, and even more preferably above the combined temperature of the melting point of layer A 812 and 40°C. Therefore, when the melting point of layer A 812 is 217°C, the temperature of the heated metal plate 5 is more preferably above 237°C, even more preferably above 247°C, even more preferably above 252°C, and even more preferably above 257°C. If the temperature of the heated metal plate 5 is above the combined temperature of the melting point of layer A 812 and 20°C, the viscosity of layer A 812 can be effectively reduced, thus improving the adhesion to the metal plate 5.
[0282] The temperature of the heated metal plate 5 is preferably below the combined temperature of the melting point of layer B 811 and 10°C, more preferably below the combined temperature of the melting point of layer B 811 and 8°C, and even more preferably below the combined temperature of the melting point of layer B 811 and 7°C. Therefore, when the melting point of layer B 811 is 255°C, the temperature of the heated metal plate 5 is more preferably below 265°C, even more preferably below 263°C, and even more preferably below 262°C. If the temperature of the heated metal plate 5 is below the combined temperature of the melting point of layer B 811 and 10°C, excessive melting of the crystals in layer B 811 can be avoided, thus preventing an excessive decrease in the heat resistance of the biaxially oriented polyester film 81. It should be noted that the temperature of the heated metal plate 5 can also be below the melting point of layer B 811.
[0283] <1.4.3. Cooling Process>
[0284] The preferred method for manufacturing the laminate 4 includes a step of cooling a metal plate 5 to which a coating substitute film 8 or a composite film 7 is pressed. Cooling suppresses recrystallization, thus preventing the crystallinity of at least layer A 812 after lamination from becoming too high. Therefore, it prevents the adhesion to the metal plate 5 from becoming too low. Therefore, it further reduces or prevents the occurrence of the coating substitute film 8 peeling off from the metal plate 5, especially after the laminate 4 has been stamped. As an example of a cooling method, water cooling of the metal plate 5 to which the coating substitute film 8 or the composite film 7 is pressed can be described. Examples of water cooling methods include immersing the metal plate 5 to which the coating substitute film 8 or the composite film 7 is pressed in a water tank, or spraying water onto the metal plate 5 to which the coating substitute film 8 or the composite film 7 is pressed. It should be noted that the water in the tank or the water sprayed can be, for example, tap water, well water, rainwater, or purified water. Chemicals may also be added to the water. The water in the tank or the water being sprayed is preferably cold water. The water temperature can be, for example, 5°C or higher, or 15°C or higher. The water temperature is preferably 60°C or lower, more preferably 45°C or lower, even more preferably 35°C or lower, and even more preferably 30°C or lower.
[0285] In order to effectively suppress recrystallization, it is preferable to start cooling within 5 seconds after pressing the heated metal plate 5 with the coating substitute film 8 or composite film 7 (for example, immersing the metal plate 5 with the coating substitute film 8 or composite film 7 with water within 5 seconds after pressing), more preferably within 3 seconds, and even more preferably within 2 seconds.
[0286] <2. Molded Products>
[0287] The molded article of this embodiment can be obtained by stamping the laminate 4. As a stamping method, cold stamping is preferred. Cold stamping can be, for example, deep drawing or convex forming. It should be noted that if the surface protective layer 84 of the laminate 4 is not completely cured, the surface protective layer 84 can be cured as needed after stamping.
[0288] Molded articles can be used in vehicles, ships (e.g., motorboats), home appliances, and audio products. Vehicles are preferred. Examples of vehicles include automobiles, motorcycles, rail vehicles, and aircraft. Automobiles and motorcycles are preferred. When using the molded article in a vehicle, it is preferable to use it as an exterior part. As an exterior part, an exterior panel is preferred, and more preferably an automobile exterior panel. It should be noted that the molded article can also be used as a construction component or a steel sheet product.
[0289] <3. Various modifications can be made to the above implementation methods>
[0290] Various modifications can be made to the above embodiments. For example, one or more of the following variations can be selected to modify the above embodiments.
[0291] In the above embodiment, the laminate 4 is described as including a protective film 9. However, this embodiment is not limited to this configuration. That is, the laminate 4 may not include a protective film 9.
[0292] In the above embodiments, the configuration of the coating replacement film 8 including the adhesive layer 82 has been described. However, this embodiment is not limited to this configuration. That is, the laminate 4 may also not include the adhesive layer 82.
[0293] The above embodiment describes a configuration where the coloring layer 83 is disposed on the adhesive layer 82. However, this embodiment is not limited to this configuration. Other layers may exist between the adhesive layer 82 and the coloring layer 83.
[0294] The above embodiment describes a configuration in which the surface protective layer 84 is disposed on the coloring layer 83. However, this embodiment is not limited to this configuration. Other layers may exist between the coloring layer 83 and the surface protective layer 84.
[0295] The above embodiment describes a configuration where the protective film 9 is disposed on the surface protective layer 84. However, this embodiment is not limited to this configuration. Other layers may exist between the surface protective layer 84 and the protective film 9.
[0296] In the above embodiments, the configuration of the biaxially oriented polyester film 81 as a two-layer structure has been described. However, this embodiment is not limited to this configuration. For example, the biaxially oriented polyester film 81 may include other layers between layer B 811 and layer A 812. The biaxially oriented polyester film 81 may include other layers between layer B 811 and coloring layer 83.
[0297] Example
[0298] The following examples and comparative examples illustrate the present invention in more detail. Unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".
[0299] <Measurement or Evaluation Methods>
[0300] (A) Intrinsic viscosity
[0301] 0.2 g of polyester was dissolved in 50 ml of a mixed solvent of phenol and 1,1,2,2-tetrachloroethane (60 / 40 (mass ratio)), and the viscosity was measured using an Orstauld viscometer at 30 °C. The unit is dL / g.
[0302] (B) Melting point (Tm)
[0303] In the differential scanning calorimetry (DSC) determination of polyester, the polyester was heated to 300°C and melted for 5 minutes, then quenched with liquid nitrogen. Using a DSC-60 differential scanning calorimeter (manufactured by Shimadzu Corporation), 10 mg of the quenched polyester was heated at a rate of 20°C / min. From the resulting DSC curve, the endothermic peak temperature based on crystal melting was determined as the melting point. Here, the endothermic peak is an endothermic peak of 0.05 J / g or higher that occurs at a temperature higher than the baseline shift corresponding to the glass transition temperature, associated with crystal melting.
[0304] On the other hand, the melting point of layer A is determined by cutting a sample from layer A, and all other samples are determined using the same method. Specifically, the sample cut from layer A is heated to 300°C and melted for 5 minutes, then quenched with liquid nitrogen. Using a DSC-60 differential scanning calorimeter (manufactured by Shimadzu Corporation), 10 mg of the quenched sample is heated at a rate of 20°C / min. From the resulting DSC curve, the endothermic peak temperature based on crystal melting is determined as the melting point.
[0305] The melting point of layer B is determined by cutting a sample from layer B, and otherwise using the same method as for the melting point of layer A.
[0306] (C) Thickness of each layer of the coating replacement film
[0307] A sample measuring 2 mm in the flow direction and 2 cm in the width direction was cut from the coating substitute film, fixed into an embedding capsule, and then embedded in epoxy resin. The embedded sample was then cut perpendicularly along the width direction using a microtome (Reichert-Jung Supercut) to obtain 50 μm thick film sections. Observation and imaging were performed using a scanning electron microscope (Hitachi 4300SE / N) at an accelerating voltage of 20 kV. The thickness of each layer was measured from the photographs, and the average thickness at 5 points was calculated for each layer.
[0308] (D) Plane Orientation Coefficient
[0309] Based on JIS K 7142-1996 Method A, using sodium D-rays as the light source and an Abbe refractometer, the refractive indices (Nx) in the flow direction, (Ny) in the width direction, and (Nz) in the thickness direction of layers A and B of a biaxially oriented polyester film that has not undergone easy-bonding treatment were measured. Based on this, the planar orientation coefficient ΔP of each layer was calculated using the following formula.
[0310] Orientation coefficient ΔP=(Nx+Ny) / 2-Nz
[0311] (E) Thermal shrinkage rate
[0312] To determine the thermal shrinkage rate in the MD direction, five test pieces, each 10 mm wide and 150 mm long, were cut from an untreated biaxially oriented polyester film. The length direction of these test pieces was aligned with the flow direction of the biaxially oriented polyester film, i.e., the MD direction. A pair of markings, spaced 100 mm ± 2 mm apart, were marked in the center of each test piece. The spacing between the markings (i.e., the interval between the two markings) before heating was measured with an accuracy of 0.1 mm. The test pieces were suspended without load in a hot air dryer (ESPEC CORP., PHH-202) and then heated at 150°C for 15 minutes. After removing the test pieces from the thermostatic bath and cooling to room temperature, the spacing between the markings was measured with an accuracy of 0.1 mm. Based on this, the thermal shrinkage rate in the MD direction was calculated using the following formula.
[0313] Heat shrinkage rate (%) = {(L0-L) / L0} × 100
[0314] Here, L is the spacing between the markings after heat treatment, and L0 is the spacing between the markings before heat treatment. As mentioned above, the average value of the five test pieces is substituted into L and L0.
[0315] The thermal shrinkage rate in the TD direction was determined using the same method as that in the MD direction. Specifically, five test pieces, each 10 mm wide and 150 mm long, were cut from a biaxially oriented polyester film without any bonding treatment. The length direction of these test pieces was aligned with the width direction of the biaxially oriented polyester film, i.e., the TD direction. A pair of markings with a spacing of 100 mm ± 2 mm was marked in the center of each test piece. The spacing between the markings (i.e., the interval between the two markings) before heating was measured with an accuracy of 0.1 mm. The test pieces were suspended without load in a hot air dryer (ESPEC CORP., PHH-202) and then heated at 150°C for 15 minutes. After removing the test pieces from the thermostatic bath and cooling to room temperature, the spacing between the markings was measured with an accuracy of 0.1 mm. Based on this, the thermal shrinkage rate in the TD direction was calculated using the above formula.
[0316] (F) X-ray diffraction
[0317] Using CuKα rays as the X-ray source, the X-ray diffraction intensity was determined by multiple peak separation under the following conditions: divergence slit 1 / 2°, scattering slit 1 / 2°, receiving slit 0.15 mm, scanning speed 5° / min, and incident angle 0.1°. A metal plate (specifically, a galvanized steel plate described later) with a biaxially oriented polyester film bonded to it was used as the sample. X-rays were irradiated onto the sample (i.e., the metal plate with the biaxially oriented polyester film bonded to it) along the flow direction of the biaxially oriented polyester film. The integrated intensity of the diffraction peak representing the (1-10) plane of polyethylene terephthalate was then calculated relative to the integrated intensity of the diffraction peak representing the (100) plane of polyethylene terephthalate (hereinafter, this ratio is sometimes referred to as "(1-10) plane / (100) plane"). It should be noted that in the biaxially oriented polyester film, the (100) plane is a crystal plane containing benzene rings. The (100) face is approximately parallel to the face of the biaxially oriented polyester film (which may also be referred to as the "main face").
[0318] (G) Image Deformation
[0319] A zinc alloy-coated steel sheet (hereinafter sometimes referred to as "galvanized steel sheet") with a coating substitute film and heated to the temperatures shown in Table 1 or Table 2 was pressed together. The galvanized steel sheet with the coating substitute film was immersed in a water bath for 2 seconds after pressing. It was then cooled to room temperature. Test plates with a width of 180 mm and a length of 180 mm were cut from the galvanized steel sheet with the coating substitute film. For deep drawing the test plates, a die with a drawing ratio of 1.3 was used, and the periphery of the test plate was held under a load of 15 t, followed by a room temperature stamping of the center of the test plate at 100 t. The deep-drawn test plate, i.e., the formed product, was placed on a floor 50 cm horizontally offset from directly below a fluorescent lamp located 2.5 m above the floor. The formed product was placed on the floor with its bottom inner surface facing upwards; specifically, the hard coating of the coating substitute film on the bottom inner surface of the formed product was facing the fluorescent lamp. Visually observe the image of the fluorescent lamp projected onto the molded product, and then determine the degree of image distortion according to the following criteria.
[0320] Judgment A: The image of the fluorescent lamp has almost no distortion.
[0321] Judgment B: The image of the fluorescent lamp is locally distorted.
[0322] Criterion C: The image of the fluorescent lamp is distorted overall.
[0323] (H) Evaluation of adhesion after cold stamping
[0324] In the "image deformation" process, a cut marked with an "X" (cross) is made in the center of the molded article (i.e., the deep-drawing test plate), specifically on the inner bottom surface of the molded article. Specifically, an X-shaped cut is made using a cutting tool, extending not only to the coating replacement film but also to the galvanized steel sheet, onto the inner bottom surface of the molded article. The molded article is then placed in a cooking processor and treated at 120°C, 0.2 MPa, for 2 hours. For the treated molded article, the adhesion of the coating replacement film (specifically, the adhesion between the coating replacement film and the galvanized steel sheet) is determined according to the following criteria.
[0325] Judgment A: No peeling
[0326] Judgment B: Partial peeling (whitening observed in localized areas)
[0327] Criterion C: Delamination present (overall whitening observed)
[0328] <Raw materials for biaxially oriented polyester film>
[0329] The following resin composition is used to form layer B.
[0330] Resin Composition A
[0331] As resin composition A, a mixture of resin B and resin C is used.
[0332] Resin B: PET resin, IV=0.75 dL / g, melting point 255℃, 97.0 parts by weight
[0333] Resin C: PET resin containing 0.036% by weight of silica particles (average particle size 1.7 μm), IV = 0.75 dL / g, melting point 255℃, 3.0 parts by weight.
[0334] Resin composition D
[0335] As resin composition D, a mixture of resin E and resin F is used.
[0336] Resin E: PET resin, IV=0.62 dL / g, melting point 255℃, 90.0 parts by weight
[0337] Resin F: PET resin containing 0.72% by weight of silica particles (average particle size 2.7 μm), IV = 0.62 dL / g, melting point 255℃, 10.0 parts by weight.
[0338] Resin Composition G
[0339] As resin composition G, a mixture of resin F and resin H is used.
[0340] Resin F: PET resin containing 0.72% by weight of silica particles (average particle size 2.7 μm), IV = 0.62 dL / g, melting point 255℃, 10 parts by weight
[0341] Resin H: A copolyester resin comprising 92.1 mol% polyethylene terephthalate units and 7.9 mol% polyethylene isophthalate units, IV = 0.62 dL / g, melting point 233℃, 90 parts by weight.
[0342] The following resin is used to form layer A.
[0343] Resin I
[0344] A copolyester resin with 86.0 mol% ethylene terephthalate units and 14.0 mol% ethylene isophthalate units, IV = 0.70 dL / g, melting point 217℃.
[0345] Resin J
[0346] A copolyester resin with 89.0 mol% terephthalate units and 11.0 mol% terephthalate units, IV = 0.63 dL / g, melting point 225℃.
[0347] Resin K
[0348] A copolyester resin with 80.0 mol% ethylene terephthalate units and 20.0 mol% ethylene isophthalate units, IV = 0.63 dL / g, melting point 198℃.
[0349] <Example 1>
[0350] Production of biaxially oriented polyester film with easy-to-bond treatment
[0351] The molding material for layer B (specifically, resin composition A) is melted at 280°C using a first extruder, and the molding material for layer A (specifically, resin I) is melted at 280°C using a second extruder. These molding materials are stacked in a die and extruded into a cooling roller. The unstretched sheet cured in the cooling roller is stretched 3.0 times along the flow direction at 80°C. The surface of layer B is coated with an epoxy adhesive (i.e., an adhesive containing epoxy resin), and stretched 3.5 times along the width direction at 130°C. The sheet stretched in the width direction is heat-set at 215°C, followed by a 5% relaxation process in the width direction. This yields a biaxially oriented polyester film with a layer thickness of 15 μm (A layer) and a layer thickness of 35 μm (B layer) after easy-bonding treatment. The thickness of the easy-bonding layer in the biaxially oriented polyester film after easy-bonding treatment is 30 nm. It should be noted that the biaxially oriented polyester film after easy-bonding treatment is wound into rolls.
[0352] Fabrication of coating alternative films
[0353] While drawing out the easily bonded biaxially oriented polyester film, a coating liquid is applied to the easily bonded layer of the biaxially oriented polyester film using a comma coater, and then dried in a drying oven at 90°C. The coating liquid used contains an acrylate-based resin, 10% by mass of aluminum pigment, and a solvent coating with 35% by mass of non-volatile components. This yields a preform film, namely, a preform film having an easily bonded biaxially oriented polyester film and a 20 μm thick colored layer disposed on the easily bonded layer. In other words, a preform film having a biaxially oriented polyester film, an easily bonded layer, and a 20 μm thick colored layer is obtained. It should be noted that the preform film is wound into a roll.
[0354] While the preform is being extracted, the hard coating material (described later) is applied to the coloring layer using a comma coater to achieve a hard coating thickness of 30 μm. The coating is then thoroughly dried in a drying oven at 90°C.
[0355] The coating replacement film is obtained by following these steps. The hard coating that constitutes the coating replacement film is in a semi-cured state, that is, not fully cured.
[0356] Hard coatings
[0357] 150 parts by weight of methyl isobutyl ketone were added to a four-necked flask equipped with a condenser, stirrer, thermometer, and nitrogen inlet. The mixture was heated while stirring under a nitrogen atmosphere. When the temperature inside the flask reached 74°C, this temperature was maintained as the synthesis temperature. Over 2 hours, a monomer solution was added dropwise to the flask, consisting of 3 parts by weight of methyl methacrylate, 82.54 parts by weight of n-butyl methacrylate, 12.85 parts by weight of 4-hydroxybutyl acrylate, 0.61 parts by weight of methacrylic acid, 1 part by weight of FANCRYL FA-711MM (manufactured by Hitachi Chemical Co., Ltd., pentamethylpiperidinyl methacrylate), and 0.1 parts by weight of azobisisobutyronitrile. One hour after the monomer addition was completed, 0.02 parts by weight of azobisisobutyronitrile were added every hour, continuing the reaction until the unreacted monomer content in the monomer solution fell below 1%. Once the unreacted monomer content fell below 1%, the mixture was cooled to terminate the reaction, yielding an acrylic copolymer solution with a solid content of approximately 40% by weight. In the acrylic copolymer solution, 59.9 parts by weight (solid mass) of DURANATE "P301-75E" (a polyisocyanate of hexamethylene diisocyanate manufactured by Asahi Kasei Chemicals Co., Ltd.) as a polyisocyanate compound were added, and methyl isobutyl ketone was further added in such a way that the solid content was 30% by weight and stirred to obtain a coating for hard coating.
[0358] Fabrication of galvanized steel sheets with a coating alternative film.
[0359] A coating substitute film is pressed together with a galvanized steel sheet (specifically, a 0.6 mm thick steel sheet coated with zinc alloy) heated to the temperatures shown in Table 1. The galvanized steel sheet with the coating substitute film pressed together is then immersed in a water bath (specifically, a bath filled with water at 23°C) for 2 seconds after pressing, thereby cooling to room temperature. This yields a galvanized steel sheet with a coating substitute film pressed together.
[0360] Production of biaxially oriented polyester film without easy-bonding treatment
[0361] Without performing easy-bond treatment, a biaxially oriented polyester film without easy-bond treatment is produced using the same method as a biaxially oriented polyester film with easy-bond treatment.
[0362] <Examples 2-4 and Comparative Examples 1-6 (strictly speaking, Comparative Examples 1-2 and 4-6)>
[0363] As the resin used to form layer A, the resin described in Table 1 or Table 2 is used, and the film-forming conditions (stretch ratio, stretching temperature, heat setting temperature) described in Table 1 or Table 2 are adopted. The thicknesses of layer A and layer B are as described in Table 1 or Table 2. Otherwise, biaxially oriented polyester films with easy-bonding treatment, coating alternative films, and biaxially oriented polyester films without easy-bonding treatment are prepared by the same method as in Example 1.
[0364] The galvanized steel sheet is heated to the temperature shown in Table 1 or Table 2. Otherwise, the galvanized steel sheet with a coating alternative film is produced by means of the same method as in Example 1.
[0365] <Results>
[0366] The table below contains the results.
[0367] [Table 1]
[0368]
[0369] [Table 2]
[0370]
[0371] The (1-10) plane / (100) plane values in these tables are obtained by measuring the X-ray diffraction intensity using galvanized steel sheets with easily bonded biaxially oriented polyester films pressed onto them as samples.
[0372] Based on the use of galvanized steel sheet with a coating substitute film as a sample, the X-ray diffraction intensity was measured using the above method. The results showed that the (1-10) plane / (100) plane was the same as the (1-10) plane / (100) plane when using galvanized steel sheet with a biaxially oriented polyester film that has been press-fitted for easy bonding as a sample.
[0373] In Comparative Example 1, where the ratio of (1-10) plane to (100) plane is 0.12, the adhesion is C. This is attributed to the excessively high crystallinity, resulting in low adhesion to the metal plate.
[0374] In Comparative Example 4, where the ratio of (1-10) plane to (100) plane is 0.07, the adhesion is B. This is attributed to the excessively high crystallinity, resulting in low adhesion to the metal plate.
[0375] As described above, the adhesion of Comparative Example 4 is superior to that of Comparative Example 1. In this regard, since the thermal shrinkage rate of Comparative Example 4 is less than that of Comparative Example 1, it is believed that in Comparative Example 4, the thermal shrinkage during the pressing of the galvanized steel sheet with the coating substitute film is small, and therefore, the reduction in adhesion to the galvanized steel sheet due to thermal shrinkage is small. Furthermore, since the planar orientation coefficient of layer A in Comparative Example 4 is less than that of layer A in Comparative Example 1, it is believed that layer A flows easily during the pressing of the galvanized steel sheet with the coating substitute film in Comparative Example 4.
[0376] In Comparative Example 5, where the ratio of (1-10) surface to (100) surface is 0.11, the adhesion is C.
[0377] As described above, the adhesion of Comparative Example 5 is worse than that of Comparative Example 4. The thermal shrinkage rate of Comparative Example 5 is greater than that of Comparative Example 4. Therefore, it is believed that in Comparative Example 5, the thermal shrinkage during the pressing of the galvanized steel sheet with the coating substitute film is greater, and thus, the reduction in adhesion to the galvanized steel sheet due to thermal shrinkage is greater.
[0378] In Comparative Example 6, the ratio of (1-10) side to (100) side was 1.48, but the adhesion was B. This is believed to be because the thermal shrinkage rate was significantly large, resulting in a significant thermal shrinkage when the galvanized steel sheet was pressed with the coating replacement film. Consequently, the reduction in adhesion to the galvanized steel sheet, which may be caused by thermal shrinkage, was also significantly large.
[0379] In Comparative Example 2, where the ratio of the (1-10) plane to the (100) plane is 1.21, the image distortion is C. This is believed to be due to the low crystallinity, resulting in poor heat resistance of the biaxially oriented polyester film. In Comparative Example 6, where the ratio of the (1-10) plane to the (100) plane is 1.48, the image distortion is also C.
[0380] In Example 4, the ratio of (1-10) plane to (100) plane is 0.32, but the image distortion is B. This is believed to be because the orientation coefficient of layer B in Example 4 is small. Therefore, when the galvanized steel sheet is pressed with the coating substitute film, the heat received by the coating substitute film (i.e., the heat during lamination) causes wrinkles or bubbles to be generated in the coating substitute film.
[0381] In Comparative Example 4, the ratio of (1-10) plane to (100) plane is 0.07, but the image distortion is B. This is believed to be because the plane orientation coefficient of layer B is small, thus causing wrinkles or bubbles to form in the coating substitute film due to the heat during lamination.
[0382] It should be noted that the image deformation of both Example 4 and Comparative Example 4 is B, but the degree of deformation of Example 4 is smaller than that of Comparative Example 4.
[0383] In Comparative Example 5, the ratio of (1-10) plane to (100) plane is 0.11, but the image distortion is B. This is believed to be because the plane orientation coefficient of layer B is small, thus causing wrinkles or bubbles to form in the coating substitute film due to the heat during lamination.
[0384] Industrial availability
[0385] This invention can provide laminates, molded articles, vehicle exterior parts, etc., and therefore can be used in industry.
[0386] Explanation of reference numerals in the attached figures
[0387] 4…Laminated body, 5…Metal plate, 7…Composite film, 8…Coating replacement film, 9…Protective film, 81…Biaxially oriented polyester film, 82…Adhesive layer, 83…Coloring layer, 84…Surface protective layer, 811…Layer B, 812…Layer A.
Claims
1. A laminate comprising: Metal plate; and A coating alternative film laminated onto the metal plate. The coating replacement film comprises a biaxially oriented polyester film, a coloring layer, and a surface protective layer. The biaxially oriented polyester film comprises a first layer and a second layer. The first layer is located between the second layer and the coloring layer. The first layer contains a first polyester comprising alkylene terephthalate units. The second layer contains a second polyester comprising alkylene terephthalate units. The melting point of the first layer is higher than that of the second layer. In the X-ray diffraction pattern of the laminate, the integrated intensity of the diffraction peak representing at least the alkyl terephthalate units originating from the first polyester and the alkyl terephthalate units originating from the second polyester, relative to the integrated intensity of the diffraction peak representing at least the alkyl terephthalate units originating from the first polyester and the alkyl terephthalate units originating from the second polyester, is 0.2 or more and 1.0 or less, and the (1-10) plane is a crystal plane as follows: 。 2. The laminated body according to claim 1, wherein, The coating replacement film also includes an adhesive layer. The adhesive layer is located between the biaxially oriented polyester film and the coloring layer.
3. The laminated body according to claim 2, wherein, The thickness of the adhesive layer is greater than 10 nm and less than 200 nm.
4. The laminated body according to claim 1, wherein, The coloring layer contains resin and colorant.
5. The laminated body according to claim 1, wherein, The alkyl terephthalate unit of the first polyester comprises a polyethylene terephthalate unit. The alkyl terephthalate unit of the second polyester comprises a polyethylene terephthalate unit. The (1-10) facets are at least derived from the polyethylene terephthalate units of the first polyester and the polyethylene terephthalate units of the second polyester. The (100) facet is at least derived from the polyethylene terephthalate unit of the first polyester and the polyethylene terephthalate unit of the second polyester.
6. The laminate according to claim 5, wherein, When the repeating unit of the first polyester is set to 100 mol%, the ethylene terephthalate unit is 85 mol% or more. When the repeating unit of the second polyester is set to 100 mol%, the ethylene terephthalate unit is 60 mol% or more.
7. The laminate according to claim 1, further comprising a protective film, The laminate consists of the metal plate, the coating replacement film, and the protective film stacked sequentially.
8. The laminate according to claim 1, used for manufacturing vehicle exterior parts.
9. A molded article, which is formed by stamping the laminated body according to any one of claims 1 to 8.
10. A vehicle exterior trim component, which is formed by stamping a laminated body according to any one of claims 1 to 8.
11. A method for manufacturing a laminate, which is the method for manufacturing a laminate according to any one of claims 1 to 8, comprising: The process of heating the metal plate; as well as The process of pressing the heated metal plate with the coating replacement film or composite film. The composite film includes the coating replacement film and a protective film disposed on the surface protective layer of the coating replacement film.
12. The method for manufacturing a laminate according to claim 11, further comprising a step of starting cooling within 5 seconds after pressing the metal plate with the coating alternative film or the composite film.
13. The method for manufacturing a laminate according to claim 11, wherein, The planar orientation factor of the first layer of the coating replacement film or the composite film pressed onto the metal plate is 0.165 or higher and 0.180 or lower. The planar orientation coefficient of the second layer of the coating replacement film or the composite film pressed onto the metal plate is 0.100 or higher and 0.135 or lower.
Citation Information
Patent Citations
Laminated film
JP2020192787A
